Consumer complaint and redress-seeking behavior of selected UP students - Bartolome, Jose Marti D.
This study described the consumer complaint and redress-seeking behavior of selected UP students, the outcome of their previous complaint experiences and their perceived barriers to complaining. A total of 31 registered students from the University of the Philippines-Diliman were selected and included as respondents through network sampling. This study made use of an open-ended survey questionnaire followed by an interview to clarify and probe the answers. Results showed that student consumers have experienced four sources of grievances, namely: product design or service failure, dissatisfaction in the delivery, price and payment problems and dissonance with personal experience. Findings revealed that these experiences are mainly discontent from consuming food products, food-related services and public transportation. They were motivated to complain mostly because of aggravating circumstances such as unfriendly wait staff, the need to get their money's worth and the presence of product/service warranty/guarantee or quality standard. Results also showed that the students were discouraged from taking action due to time constraints, indifference towards the system of redress and when they feel that the situation is not severe to warrant complaint. In terms of the manner of complaining, results showed that students preferred to complain verbally to any attending personnel and they shared to have communicated their concerns in a calm and normal speaking tone of voice. In general, the students were given redress and were satisfied with the outcome of their complaints most of the time. This suggests that sellers and service providers do listen and act on the complaints. Based on the students' experiences, it was found that they perceived that following barriers to complain: time constraints, lack of confidence on the part of the consumer, perceived lack of evidence and justification to complain and indifference in the complaint process.